2022
DOI: 10.13057/biodiv/d230445
|View full text |Cite
|
Sign up to set email alerts
|

Role of siamang (Symphalangus syndactylus) as seed dispersal agent in a Sumatran lowland tropical forest

Abstract: Abstract. Adyn MF, Sibarani MC, Utoyo L, Surya RA, Sedayu A. 2022. Role of siamang (Symphalangus syndactylus) as seed dispersal agent in a Sumatran lowland tropical forest. Biodiversitas 23: 2101-2110. Seed dispersal is mutualistic interaction between angiosperms and dispersal agents. One of the important dispersers for lowland tropical forests, including in Bukit Barisan Selatan National Park (BBSNP), is siamang (Symphalangus syndactylus Raffles, 1821). This study aimed to determine the seed dispersal pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…The dominant food given by animal caretakers is fruit. This is because siamang is a frugivorous animal whose primary food is fruit to meet its nutritional needs [12]. The parts of the plant consumed by siamang are varied.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant food given by animal caretakers is fruit. This is because siamang is a frugivorous animal whose primary food is fruit to meet its nutritional needs [12]. The parts of the plant consumed by siamang are varied.…”
Section: Discussionmentioning
confidence: 99%
“…The largest D. celebica tree in the Karst forest had only reached a diameter of 26.56 cm and was starting to bear fruit. The slight uptick in the population of several primary tree species in the Karst forest, including D. celebica, Diospyros spp., S. lanceolata, and G. balica, came from the germination of seeds brought by dispersal agents to this area (Corlett and Hau 2000;Adyn et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that seed dispersal distance is affected by the degree of habitat fragmentation (Nield et al 2020). In the case of gibbon dispersal, the average distance of seeds that can be spread is about 223.9 m from the parent tree (Adyn et al 2022). These descriptions are one of the reasons the number of species and the density of individual trees and their young are higher in pine forests adjacent to natural forests than those far from natural forests.…”
Section: The Relations Of the Existence Of Natural Forest And Vegetat...mentioning
confidence: 99%